Senior High Schools Teachers’ Perception on Teaching English through Online Platforms during The Lock Down Policy for School due to Covid 19 Period - Witri Handayani; Baetty Baetty; Difiani Apriyanti; Dhini Aulia; Nini Wahyuni (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2022)
Online learning have changed its identity and purposes because of the pandemic covid-19 issue which creates the situation where online learning through the online platform media is obligated due to lock down policy for school. The main aim of this study is to observe the teachers perception on teaching English through online platforms during the covid-19 period. Beside, the evaluation of the implementation of the online learning through the online platform is also being emphasiszed. The participants of this study are the Senior Hight School English teachers on West Sumatera which have passed the proffesional certification for teachers. The result of study shows that the teachers’ perception through online platform has changed. Before the pandemic, some of them found that teaching by using online platform is useful and more interesting bacuse it combined with classroom activity. However, during the pandemic where the online platform is harsly required due to lockdown policy for school, the teachers found some obstacles in implementing the online learning. The result of this study will be used for further study about teaching English through online platform.